ANATOMI DAN IDENTIFIKASI SEMBILAN BELAS JENIS KAYU DARI SULAWESI - Y I Mandang; Nenny Sumarliaai (Jurnal Penelitian Hasil Hutan, 1989)
Gross  and  anatomical   features   of  nineteen   wood  species  from   Sulawesi  belonging  to 15 genera and  11 family were observed,   described  and  then compared  for identification.   A dichotomous key  for identification   were also consructed.Upright  cells with  pointed   end  were discovered  in  the xylary   ray  tissue of Koordersiodendron pinnatum Merr.  This feature   were  never observed   in  any  other   wood  species.The  occurence of crystals  in parenchyma of Palaquium  proved  not  to be constant,  so it should  be used for identification of  the genus in positive  sense only.